Memahami Bangsa-bangsa Lain dalam Injil Matius - Putra, Adi (BIA, 2018)
This article described one of the uniqueness of the Gospel of Matthew, namely: the emergence of systemic and consistent elements of other nations (gentile). Though Matthew's Gospel is a gospel written for Jews with an emphasis on fulfilling the Old Testament in Jesus and His ministry. Then, why are the elements of other nations in it? This paper answers it by looking more at the salvation (soteriology) aspects designed by God and also includes other nations in it. Abstrak: Artikel ini menjelaskan salah satu keunikan dari Injil Matius, di mana secara sistematis dan konsisten menjelaskan unsur bangsa-bangsa lain (gentile). Meskipun injil Matius ditulis kepada orang Yahudi dengan sebuah penekanan penggenapan PL dalam Yesus dan pelayanan-Nya. Lalu, mengapa unsur bangsa-bangsa lain dijelaskan secara konsisten dan sistematis di dalamnya? Penelitian ini menjawabnya dengan melihat lebih kepada aspek keselamatan yang telah didesain oleh Allah juga bagi bangsa-bangsa lain